Key Links in Network Interactions: Assessing Route-Specific Travel Restrictions in China during the COVID-19 Pandemic - Xi Chen; Yun Qiu; Wei Shi; Pei Yu (Institute of Labor Economics (IZA), 2022)
We consider a model of network interactions where the outcome of a unit depends on the outcomes of the connected units. We determine the key network link, i.e., the network link whose removal results in the largest reduction in the aggregate outcomes, and provide a measure that quantifies the contribution of a network link to the aggregate outcomes, which complements the intercentrality measure of the key network node proposed by Ballester, Calvó-Armengol, and Zenou (2006). We provide an example examining the spread of Covid-19 in China. Travel restrictions were imposed to limit the spread of infectious diseases. As uniform restrictions can be inefficient and incur unnecessarily high costs, we examine the design of restrictions that target specific travel routes. Our approach may be generalized to multiple countries to guide policies during epidemics ranging from ex ante route-specific travel restrictions to ex post health measures based on travel histories, and from the initial travel restrictions to the phased reopening.
Keywords: C21; I18; D85; H75; 330; network interactions; key network links; COVID-19; transmission